Nematode Management in Okra - J.W. Noling (EDIS)
Plant-parasitic nematodes are small, microscopic roundworms that live in the soil and attack the roots of plants. Crop production problems induced by nematodes therefore generally occur as a result of root dysfunction; nematodes reduce rooting volume and the efficiency with which roots forage for and use water and nutrients. Many different genera and species of nematodes can be important to crop production in Florida. In many cases a mixed community of plant-parasitic nematodes is present in a field, rather than having a single species occurring alone. Okra is infamous for its susceptibility to root-knot nematodes; it is also extremely sensitive to sting nematodes. Because of this, okra should not be planted in land known to have severe problems with these nematodes in recent crops. First published March 1999.